A Life Skills Assessment Scale for High School Students in Tehran - Saraee, Soheila; Shabani, Somayeh; Pasnak, Robert (Advances in Social Sciences Research Journal, 2020)
A life skills questionnaire was developed based on existing theories. The content validity of the questions was evaluated by educational experts. The resulting life skills questionnaire had 83 questions and ten subscales: empathy, emotion regulation, self-awareness, problem solving, effective communication, interpersonal communication, stress and critical thinking, creative thinking and decision making. It had good reliability (r = .91) and validity. The confirmatory factor analysis confirmed the proposed ten factor model of the questionnaire. Given its reliability and validity, this scale of life skills can be used as a tool by researchers.